Climate Change and Agricultural Interregional Trade Flows in the People's Republic of China - Tun Lin; Xiaoyun Liu; Guanghua Wan; Xian Xin; Yongsheng Zhang (Asian Development Bank (ADB), 2011)
The impacts of climate change on agricultural production in the People's Republic of China (PRC) are significant, and differ across regions and crops. The substantial regional differences will induce changes in the agricultural interregional trade pattern. In this paper, we investigate the climate change impacts on this trade pattern, using a computable general equilibrium model of multiple regions and multiple sectors. The results indicate that Northwest, South, Central, and Northeast PRC will see increases in the outflows of agricultural products in 2030 and 2050. Conversely, outflows from East, North, and Southwest PRC will decrease. Grain handling and transportation facilities need to be repositioned to address the changes in agricultural trade flows.
hdl:11540/2050
Keywords: 330; Klimawandel; Agrarproduktion; Interregionaler Handel; Prognose; Allgemeines Gleichgewicht; China